Low dose baclofen and standard dose acamprosate had comparable changes in brain glutamate, brain Gamma amino butyric acid (GABA) and craving among patients with alcohol dependence syndrome: A 1H-MRS based open label randomized study - Akhil Kesan; Pranjal Dey; Sourav Khanra; Samiksha Singhai; Monalisa Boro (Industrial Psychiatry Journal)
Background: Understanding of the mechanism of action of Baclofen as anticraving inalcohol dependence syndrome (ADS) is limited. Aim: Our study aimed to examine and compareearly changes in brain glutamate and GABA with Baclofen and Acamprosate among patients with alcohol dependence syndrome. Material and Methods: Forty patients with ADS were recruited with purposive sampling and were randomized into two groups using computer-generated randomization. At the end of detoxification (CIWA-Ar <10) brain glutamate and GABA were measured with proton magnetic resonance spectroscopy (1H-MRS) in the anterior cingulate cortex (ACC) of the brain along with a measure of craving (PACS). Either Acamprosate or Baclofen was started. After 25 days of starting Baclofen or Acamprosate brain glutamate and brain GABA using 1H-MRS and PACS measures were repeat measured. Results: Both groups had shown comparable changes in brain glutamate (F = 0.01, P = 0.92, ηp2 = 0.00) and GABA (F = 0.29, 26 P = 0.59, ηp2 = 0.008) and craving (F = 0.08, P = 0.77, ηp2 = 0.002) over time. Baclofen and Acamprosate showed a differential relation with the clinical characteristics of participants. Conclusion: Our study has shown comparable changes in Glutamate and GABA during the early post-detoxification period both for baclofen and acamprosate. Effects of baclofen and acamprosate might correlate differently with the clinical profile of alcohol dependence syndrome which would help in choosing a particular anticraving medication.